Diffuse preretinal infiltrates in a patient with orbital atypical T-cell lymphoproliferative infiltration masquerading posterior uveitis - Batu Oto, Bilge; Kılıçarslan, Oğuzhan; Uçar, Didar; Hagverdiyeva, Samira; Sarıcı, Ahmet Murat (GMS Ophthalmology Cases)
Purpose: To report an aggressive and rapidly progressive case of atypical T-cell lymphoproliferative infiltration both with intraocular and orbital involvement and preretinal infiltrates.Methods: Medical records and imaging of the patient were retrospectively reviewed.Case presentation: A 25-year-old woman presented first with preretinal infiltrates resembling uveitis and developed orbital and intracranial signs eventually during her evaluation. Clinical presentation worsened gradually. The patient developed bilateral proptosis, pupillary dilation and uvula deviation. Diagnostic orbital incision biopsy revealed T-cell lymphoproliferative disease. Conclusion: This case gives evidence that intraocular involvement due to T-cell lymphoproliferative disease may present as a masquerade syndrome and should be kept in mind in patients with extraordinary presentation.